High level antibody response to pandemic influenza H1N1/09 virus is associated with interferon-induced transmembrane protein-3 rs12252-CC in young adults - Qin, Q; Wang, D; Li, D; Zhao, Y; Peng, Y; Wellington, D; Dai, W; Sun, J; Liu, G; McMichael, A; Dong, T; Zhang, Y (Frontiers Media, 2018)
Background: The C allele of the interferon-induced transmembrane protein-3 (IFITM3) SNP rs12252, a common allele in South East Asia and China, is strongly associated with severe influenza infection. However, despite the high occurrence of rs12252-CC genotype in Chinese population (~25%), severe influenza infection is rare. The aim of study is to determine whether rs12252-CC individuals have pre-existing antibody responses to previous seasonal influenza infections. Cohort and method: A total 99 young healthy volunteers (18–20 years) were recruited and received an influenza seasonal Vaccination [A/Switzerland/9715293/2013(H3N2), A/California/7/2009 (pdm09H1N1) and B/Jeep/3073/2013-like virus (Flu-B)]. Plasma and gDNA was isolated from each volunteer before, and 14, 28, 180, 360, and 540 days after vaccination. Additionally, 68 elderlies (>65 years) were also recruited as a control group to compare the levels of antibodies at baseline between the young adults and the elderly. For each sample IFITM3 rs12252 genotype was determined and antibody levels in response to pdmH1N1, H3N2 and Influenza B infection were measured for each time point. Results: We found a significantly higher level of pre-existing antibodies to pandemic influenza H1N1/09 virus (pdm09H1N1) but not to H3N2 or FluB in CC donors in comparison with CT/TT donors prior to vaccination. No impact of IFITM3 genotype in boosting influenza specific antibodies in young adults within 1 year after receiving seasonal influenza vaccination was observed. In addition, there was no difference in pdm09H1N1 specific antibody levels observed in the elderly cohort between volunteers carrying different IFITM3 genotypes. Higher levels of antibodies to pdmH1N1 were observed in elderly CC carriers when compared to the young CC carriers, but this trend was not replicated in TT carriers. Conclusion: IFITM3-rs12252 CC carriers exhibit a high level of pre-existing immunity to pdm09H1N1 compared to TT carriers in the young cohort. This suggests that compensatory mechanisms exist which might contribute to viral control in patients carrying the rs12252-CC genotype who do not become sick after flu infection. However, such a potential compensatory effect appears to be lost overtime, as evidenced in the elderly cohort. If this compensatory mechanism is lost, it may make the CC carrying elderly more susceptible to severe influenza infection.